2017
DOI: 10.1128/aac.00234-17
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-Resistant mcr-1 -Positive Escherichia coli on Public Beaches, an Infectious Threat Emerging in Recreational Waters

Abstract: The emergence and rapid spread of colistin-resistant Escherichia coli carrying the mcr-1 gene have generated an urgent need to strengthen surveillance. We performed a meticulous investigation of strains of this sort, which resulted in the identification of international clones of E. coli carrying IncX4-plasmid-mediated mcr-1 and bla CTX-M genes in recreational waters of public urban beaches in cities with high tourist turnover, highlighting a new environmental reservoir.KEYWORDS MCR-1, ESBL, CTX-M, IncX4, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 17 publications
0
39
0
3
Order By: Relevance
“…There have been many reports of MCR producers in Brazil, with MCR-1 being the only variant systematically identified. These isolates were a single Salmonella enterica serotype Typhimurium isolate that was recovered from retail meat (18) and E. coli isolates recovered from chicken meat (19), from migratory penguins (20), on public beaches (21), or from patients with bloodstream infections (22,23). Also, KPC-2-producing E. coli isolates (24) and KPC-2-producing Klebsiella pneumoniae isolates belonging to ST392 and ST437 (25,26) were identified.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of MCR producers in Brazil, with MCR-1 being the only variant systematically identified. These isolates were a single Salmonella enterica serotype Typhimurium isolate that was recovered from retail meat (18) and E. coli isolates recovered from chicken meat (19), from migratory penguins (20), on public beaches (21), or from patients with bloodstream infections (22,23). Also, KPC-2-producing E. coli isolates (24) and KPC-2-producing Klebsiella pneumoniae isolates belonging to ST392 and ST437 (25,26) were identified.…”
Section: Discussionmentioning
confidence: 99%
“…mcr-type genes encode phosphoethanolamine transferases that add PEtN to the phosphate group of the lipid A moiety (at the 4= position) anchored on LPS, reduce negative charges that are present in LPS, and consequently confer resistance to polymyxins (4,(9)(10)(11)(12). The mcr-1 gene has been identified as a plasmid-mediated resistance mechanism being widely disseminated among human, animal, food, and environmental E. coli isolates (6)(7)(8)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…PFGE and/or MLST data obtained from earlier studies revealed that most mcr-1-positive E. coli isolates were clonally unrelated(8,(13)(14)(15)(16)(17)33). The combined disk test method was performed in triplicate.…”
mentioning
confidence: 99%
“…To date, mcr-1 has been observed on a wide variety of plasmid types, including IncI2, IncHI2, and IncX4 15 . Intensive screening efforts for mcr-1 have found it to be highly prevalent in a number of environmental settings, including the Haihe River in China 17 , recreational water at public urban beaches in Brazil 18 , and faecal samples from otherwise healthy individuals 19,20 . While both Brazil and China have now banned the use of colistin in agriculture, the evidence that mcr-1 can spread within hospital environments even in the absence of colistin use 19 as well as in the community 20 raises the possibility that the spread of mcr-1 will not be contained by these bans.…”
Section: Introductionmentioning
confidence: 99%